2006
DOI: 10.3189/172756506781828647
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure mapping: a new method for imaging deformation-induced microstructural features of ice on the grain scale

Abstract: ABSTRACT. This work presents a method of mapping deformation-related sublimation patterns, formed on the surface of ice specimens, at microscopic resolution (3-4 mm pixel -1 ). The method is based on the systematic sublimation of a microtomed piece of ice, prepared either as a thick or a thin section. The mapping system consists of an optical microscope, a CCD video camera and a computer-controlled xy-stage. About 1500 images are needed to build a high-resolution mosaic map of a 4.5 Â 9 cm section. Mosaics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(123 citation statements)
references
References 34 publications
5
115
0
1
Order By: Relevance
“…This process is very efficient in ice due to the natural deformation conditions of this mineral, i.e. temperatures close to its pressure melting point and deformation at low strain rates (Kipfstuhl et al, 2006). These are observable especially in comparison with fast artificial deformation in creep tests (Weikusat et al, 2009).…”
Section: Introductionmentioning
confidence: 91%
“…This process is very efficient in ice due to the natural deformation conditions of this mineral, i.e. temperatures close to its pressure melting point and deformation at low strain rates (Kipfstuhl et al, 2006). These are observable especially in comparison with fast artificial deformation in creep tests (Weikusat et al, 2009).…”
Section: Introductionmentioning
confidence: 91%
“…Thin sections were prepared according to standard procedures, allowing the surfaces to sublimate and reveal (sub)grain boundaries as etch grooves (Kipfstuhl and others, 2006). For each sample, at least two sections, one cut horizontally and the other vertically, were prepared.…”
Section: Observation Methodsmentioning
confidence: 99%
“…4b). Kipfstuhl and others (2006) showed that subgrain boundaries are revealed as grooves under controlled sublimation conditions. The dependence of sublimation/thermal grooving on misorientation was described generally by Mullins (1957) and by Saylor and Rohrer (1999) for ceramic polycrystals.…”
Section: Grain-shape Datamentioning
confidence: 99%
See 2 more Smart Citations